Effects of a high protein corn co-product as a replacement for soybean meal in calf starter grains - Skinner, Rachel Grace (My University, 2024)
Provision of a nutritionally balanced starter grain to dairy calves within the first weeks of life is essential for setting calves up for a successful weaning transition. While conventional dried distillers’ grains are an attractive protein source for most cattle diets, utilization in calf starter grains have yielded undesirable results. Evolutions in ethanol fractionation technology has brought about innovations in co-product feed ingredients which may be more applicable for use in calf starter grains. High protein corn co-products (HPCC), which are enriched with yeast bodies from fermentation, contain similar amounts of crude protein to soybean meal and may be a suitable option for calf starter grains. To assess HPCC as a substitute for soybean meal in starter grains, Holstein calves were fed starter grains from 14 to 84 d of age with either 0 (CTRL), 50 (50HPCC), or 100% (100HPCC) of the soybean meal replaced by HPCC. During the preweaning period (14 to 42 d of age), HPCC quadratically effected starter grain intake with 50HPCC calves consuming less grain than CTRL or 100HPCC calves. The HPCC inclusion increased bodyweight; however, treatment did not affect structural growth or feed efficiency. After weaning, effects of HPCC on starter grain intake were less discernable. Bodyweight and average daily gain increased with HPCC, but wither height was reduced in weaned 50HPCC calves. Males grew heavier and taller throughout the study. Plasma glucose and insulin concentrations increased with time and insulin concentration was increased by HPCC in weaned calves. There was no evidence of treatment effect on dry matter or crude protein apparent total tract digestibility in weaned calves. Males had greater apparent total tract digestibility of dry matter and crude protein of than females. Overall, these results suggest that HPCC is a suitable replacement for soybean meal in calf starter grains when supplemented with methionine and lysine.
Keywords: Starter grain; Byproducts; Distillers grains; Calf nutrition